2022
DOI: 10.1101/2022.02.01.22270285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association study of HLA with the kinetics of SARS-CoV-2 spike specific IgG antibody responses to BNT162b2 mRNA vaccine

Abstract: BNT162b2, an mRNA-based SARS-CoV-2 vaccine (Pfizer-BioNTech), is one of the most effective COVID-19 vaccines and has been approved by more than 130 countries worldwide. However, several studies have reported that the COVID-19 vaccine shows high interpersonal variability in terms of humoral and cellular responses, such as those with respect to SARS-CoV-2 spike protein immunoglobulin (Ig)G, IgA, IgM, neutralizing antibodies, and CD4+ & CD8+ T cells. The objective of this study is to investigate the kinetic c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, in silico DRB1*15:01 was predicted to have a higher number of strong binding peptides derived from the entire sequence of the SARS-CoV-2 S protein [19]. HLA associations with anti-SARS-CoV-2 S Abs had also been analyzed in 100 Japanese hospital workers [18] and DQA1:03:03 was reported to be associated with production of greater amounts of anti-SARS-CoV-2 S Abs. In that study, the association of DRB1*12:01 with higher levels of anti-SARS-CoV-2 S Abs was not reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in silico DRB1*15:01 was predicted to have a higher number of strong binding peptides derived from the entire sequence of the SARS-CoV-2 S protein [19]. HLA associations with anti-SARS-CoV-2 S Abs had also been analyzed in 100 Japanese hospital workers [18] and DQA1:03:03 was reported to be associated with production of greater amounts of anti-SARS-CoV-2 S Abs. In that study, the association of DRB1*12:01 with higher levels of anti-SARS-CoV-2 S Abs was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies on the association of HLA with levels of anti-SARS-CoV-2 S Abs have been reported [18,19]. Hence, we investigated the association of HLA polymorphisms with levels of anti-SARS-CoV-2 S-specific or neutralizing Abs in vaccinated RA patients in Japan.…”
Section: Introductionmentioning
confidence: 99%